Cancer Therapy By Targeting Hypoxia-Inducible Factor-1 - Li, Y.; Ye, D. (Current Cancer Drug Targets, 2010)
Tumors are invariably less well-oxygenated than the normal tissues from which they arise. Hypoxia-inducible factor-1 (HIF-1), a key transcriptional regulator, plays a central role in the adaptation of tumor cells to hypoxia by activating the transcription of genes, which regulate several biological processes including angiogenesis, cell proliferation, survival, glucose metabolism and migration. The expression, activity and stability of HIF-1 are not only induced in response to reduced oxygen availability but also modulated through PI-3K, MAPKs, autocrine signaling pathways, E3 ubiquitin ligases, and other regulators. The regulators and effects of HIF-1 in cancer have intensively provided us a new clue for the HIF-1 targeting anticancer therapy. This review evaluates the HIF-1 structure, the regulation mechanisms, the functions in cancer and corresponding anticancer strategies.
Keywords: angiogenesis